Probiotics for glycemic control in patients with type 2 diabetes mellitus: protocol for a systematic review - Thanitsara Rittiphairoj (Systematic Reviews, 2019)
Abstract Background Type 2 diabetes mellitus (T2DM) is a major public health problem worldwide. It is characterized by the increased concentration of glucose in the blood and leads to damage of the body system, especially blood vessels and nerves. Lifestyle modification is often combined with anti-diabetic therapy as the standard of care for T2DM to maintain the proper blood glucose and to prevent long-term diabetic complications. The role of probiotics in improving glycemic control has been investigated in several randomized controlled trials (RCTs). Previous systematic reviews and meta-analyses, including different sets of trials have concluded an overall beneficial effect of probiotics in patients with T2DM. At least two RCTs with a longer treatment duration have been published since the publication of existing reviews. Methods We will conduct a systematic review of RCTs that evaluated the effectiveness and safety of probiotics for glycemic control in T2DM patients. Primary outcomes are fasting blood glucose and glycosylated hemoglobin (A1c). Secondary outcomes are plasma insulin, blood lipid profile, adverse events, and cost associated with the intervention and hospital visits. We will search PubMed, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) in The Cochrane Library, and trial registries. Two reviewers will independently screen titles and abstracts, review full texts, extract information, and assess the risk of bias. We will summarize the results both qualitatively and statistically. We will use random-effects model for meta-analysis. Discussion This systematic review aims to examine whether probiotics are effective and safe for glycemic control in T2DM patients. Evidence generated from this review will inform clinical and public health practice and future research. Systematic review registration CRD42019121682